2020
DOI: 10.1021/acschembio.0c00169
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity Between Orthosteric Inhibitors and Allosteric Inhibitor 8-Anilino-1-Naphthalene Sulfonic Acid (ANS) in Cyclin-Dependent Kinase 2

Abstract: While kinases have been attractive targets to combat many diseases, including cancer, selective kinase inhibition has been challenging, because of the high degree of structural homology in the active site, where many kinase inhibitors bind. We have previously discovered that 8-anilino-1-naphthalene sulfonic acid (ANS) binds an allosteric pocket in cyclin-dependent kinase 2 (Cdk2). Here, we detail the positive cooperativity between ANS and orthosteric Cdk2 inhibitors dinaciclib and roscovitine, which increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…We previously discovered that the dye 8-anilino-1-naphthalene sulfonic acid (ANS) bound an unrecognized allosteric pocket within CDK2 with moderate affinity with a 5-to 10-fold enhancement in affinity in the presence of certain orthosteric inhibitors. [17][18] Despite this promise, ANS is known to be a promiscuous protein binder [19][20][21][22][23] and contains a sulfonic acid moiety that confers poor pharmacokinetic properties. However, we exploited the environmentally sensitive fluorescent nature of ANS to develop a high-throughput assay and used it to discover new chemical scaffolds with improved physicochemical properties that bind the allosteric pocket with higher affinity.…”
Section: Introductionmentioning
confidence: 99%
“…We previously discovered that the dye 8-anilino-1-naphthalene sulfonic acid (ANS) bound an unrecognized allosteric pocket within CDK2 with moderate affinity with a 5-to 10-fold enhancement in affinity in the presence of certain orthosteric inhibitors. [17][18] Despite this promise, ANS is known to be a promiscuous protein binder [19][20][21][22][23] and contains a sulfonic acid moiety that confers poor pharmacokinetic properties. However, we exploited the environmentally sensitive fluorescent nature of ANS to develop a high-throughput assay and used it to discover new chemical scaffolds with improved physicochemical properties that bind the allosteric pocket with higher affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the orthosteric Cdk2 inhibitors dinaciclib and roscovitine the affinity of ANS toward Cdk2 increased drastically. 29 Very recently, studies revealed that the optimized allosteric EGFR inhibitor JBJ-04-125-02, which shows single-agent activity in some models, can successfully bind together with osimertinib and provoke an increase in potency as compared to monotherapy. Therefore, the inhibitor combination constitutes a potential therapeutic approach for EGFR-driven NSCLC patients.…”
mentioning
confidence: 99%
“…They discovered an 8-anilino-1-naphthalene sulfonic acid (ANS) that binds an allosteric pocket in cyclin-dependent kinase 2 (Cdk2). Together with the orthosteric Cdk2 inhibitors dinaciclib and roscovitine the affinity of ANS toward Cdk2 increased drastically . Very recently, studies revealed that the optimized allosteric EGFR inhibitor JBJ-04-125-02, which shows single-agent activity in some models, can successfully bind together with osimertinib and provoke an increase in potency as compared to monotherapy.…”
mentioning
confidence: 99%
“…On the other hand, behind the orthosteric pocket, an allosteric site with separate entry has been suggested based on the binding behavior of 8-anilino-1-naphthalene sulfonic acid (ANS) molecules, denoted here as 2AN 48 . This molecule has a moderate affinity and low inhibitory potential, but it has been shown that its allosteric binding has positive cooperativity with some orthosteric inhibitors but is relatively noncooperative with ATP 49 . This allosteric site provides interesting clues for selective and/or combinatory treatments of CDK2 in cancer, but almost all cocrystallized ligands are in the orthosteric site, and the underlying assumption made here is that the set of ChEMBL ligands used in affinity prediction bind to this site.…”
Section: Resultsmentioning
confidence: 99%